Battle Royale Console Game Performance Analysis (Case Study: East Jakarta, Indonesia) - Azizah Rahim, Noorfi; Totong, Allister; Ikhsan Effendy, Muhammad; Djajasoepena, Rafie; Maindratama, Abdullah; Eryanto, Ery; Wandy, Wandy (Jurnal Teknologi, 2024)
Battle Royale (BR) genre games are still played and have massive players around the globe. They are characterized by survival and exploration elements, featuring last-man-standing gameplay that motivates players to be the final contestant in the game. This BR can now be played on single platforms and cross-platform. Apex Legends is a free-to-play hero shooter where competitors from across the frontier join forces to battle for glory, fame, and fortune. Apex Legends can be played on PlayStation, Xbox, Steam, and Switch. This research aims to understand the data captured by the game Apex Legends, played on the PlayStation 5 console and displayed on a 4K television. This data was then analyzed to measure the correlation with game performance during gameplay. This research used a quantitative method, primary data, and descriptive measurements. From the findings, it can be concluded that the FPS for this game performed well since it was still near 60 FPS (59.81) with a standard deviation of 1.07. IO could not be analyzed for network performance since no official parameters for this IO were found on the official web during the research. However, Packet Loss and Choke performed well, with an average of 0 and a standard deviation of around 0. The ping value is enormous, with a significant standard deviation gap; this can happen because the server distance is longer to Tokyo from Jakarta than Singapore. Even though the latency was high, gamers still found the matches enjoyable.